Theoretical approach of condensation for solar still. - Ahsan, Amimul; Imteaz, Monzur A.; Alam, Md. Zahangir; Haque, A. A. Mokammel; Ghazali, Abdul Halim (Nova Science Publishers, 2012)
Solar water distillation might be one of the viable options for providing drinking water for a single house or a small community in an arid, remote or coastal region. A new type of solar distillation called a Tubular Solar Still (TSS) was designed to overcome some disadvantages in the maintenance and management of a basin type still. A production model of a TSS based on a film-wise condensation theory that takes into account of thermal resistance in unsaturated humid air inside the still is presented in this chapter. The condensation coefficient due to thermal resistance is inversely proportional to the dry air pressure fraction. In the present model, the overall heat transfer coefficient between the humid air inside the still and the ambient air outside the still is used for the first time because the measurement of the ambient air temperature is easier to obtain than the inner surface temperature of the tubular cover. The analytical solution of this condensation theory could provide a good agreement with the observed production flux obtained from the field experiment and proves that the model can be used to precisely predict the production flux. A basic theoretical approach on laminar film condensation is presented first in this chapter to facilitate readers understanding before introducing the theory of film-wise condensation for a solar still.